Columella erosion secondary to nasal prongs in the neonate. (17th June 2016) - Campbell, Ewan; Pacifico, Marc D
Abstract : There is limited awareness of the risks of pressure necrosis to the columella when using nasal prongs in the neonate. Previous studies have found that signs of skin damage can occur rapidly—within days. This case report aims to illustrate a simple technique of prophylactically lowering the risk of septal injury (if prolonged use of nasal prongs is envisaged), as well as a way of conservatively treating already damaged skin areas. Routine daily skin inspections are also recommended.